“Not Here to Steal Sheep”: A Reading of the History and Politics of Catholicism in Thailand - Barry, Coeli (Archīum Ateneo, 2024)
This article investigates how Catholicism has had to evolve and adapt in order to sustain itself in Thailand. As Siam/Thailand developed through economic, political and cultural interactions with Western powers, Christianity in general and Catholicism in particular served as a site on which Thai national identity was forged in response to these interactions. Christianity was an ‘other’ against which Thai Buddhist identity coalesced yet the appeal of first Catholic and later Protestant missionary education was very strong. This article combines interpretive historical method and analysis of contemporary shifts that reflect a more assertive Thai Catholic Church. In so doing, the article offers a new reading of the place of Catholicism as a minority religion that is both aware of the risks of overtly challenging Buddhist nationalism and also confident of its place within the Thai cultural imaginary and the global Catholic networks across Asia.